Development Strategy in Munggu Tourism Village, Badung Regency, Bali Provice - Deva, Pande Made Devasmara; I Putu Sudana; Putu Sucita Yanthy (International journal of technology and education research, 2024)
This study aims to establish a growth strategy for Munggu Tourism Village, one of the tourist destinations in Mengwi Regency, Badung Province. The research began by evaluating the village's potential, examining the stages of development, and determining the elements that drove the development of the Munggu Tourism Village. This research takes a qualitative method, with data collected through observation, interviews, focus group discussions, literature reviews, and research questionnaires. The research findings suggest that the Munggu Tourism Village has a wide range of tourism potential, including mekotekan cultural attractions, dance performances, and Munggu beach tourist attractions. Munggu Tourism Village is further supported by the availability of amenities such as homestays owned and operated by the local community. The village community is also a part of a tourism awareness organization, and the village government has taken an active role in the development of the Munggu tourist village.The village community is also a part of a tourism awareness organization, and the village government has taken an active role in the development of the Munggu tourist village. Munggu Village's growth as a tourist destination is influenced by both internal and external influences. Each element is made up of five strength indicators, five weaknesses, five opportunities, and three threat indications. These elements are examined using the IFE, EFE, IE, SWOT.